Gram negative infection following plating of Tibia resulted with exposed bone and implant - Mohd Yusof, Nazri; Zulkifly, Ahmad Hafiz; Zakaria@Mohamad, Zamzuri; Che Ahmad, Aminudin; Mohammad Amin, Mohammad Azril; Awang, Mohd Shukrimi (2011)
We report four cases of gram negative infection following plating of the tibia that resulted in expose bone and metal implant which were treated in our center from March 2003 till December 2008. The incidence of Gram negative implant related infection is increasing and probably has poorer outcome. Treatment of this condition requires both bone and soft tissue reconstruction technique that is done in three stages (debridement, soft tissue reconstruction and bone reconstruction). All patient achieved union at the end of follow up.The mean union time is 9.25 months (ranges from 6 to 12 months) after the injury. At the end of follow up, only one patient had persistent infection but able to ambulate normally following fracture union).